2018
DOI: 10.1007/s00431-018-3158-2
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric outcomes of a motivational interviewing school-based randomized trial involving adolescents with overweight

Abstract: The study is called IMAGINE and is registered in Clinicaltrials.gov with the number NCT02745795. What is Known: • Although MI has been recognized as an effective counseling style for behavioral change in weight loss, there are few reports about the anthropometric outcomes of interventions with adolescents being treated for obesity/overweight. • Our study showed significant positive changes in anthropometric variables (BMI z-score, abdominal circumference, percentage of fat mass, percentage of muscular mass, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 40 publications
1
37
0
3
Order By: Relevance
“…Additionally, 80% of the rated sessions fulfilled the benchmark for good MI on the relational summary score, 67% for the technical summary score, 76% of the rated sessions fulfilled benchmarks for the summary score of percent complex reflections, and 47% of rated session the reflection to question ratio. All in all, these indicate high levels of fidelity and are comparable to other studies with high levels of fidelity to MI (Boman et al, 2018;Freira et al, 2018;Magill, Graves, et al, 2018;Owens et al, 2017;Serrano et al, 2017) and substantially higher than studies with expected lower fidelity to MI (Copeland et al, 2018;Simper, Breckon, and Kilner, 2017). The ratings indicated use of MIA's, but the general low ratings of emphasize autonomy questions the use of this important MI-technique in this study.…”
Section: Fidelity To MIsupporting
confidence: 86%
“…Additionally, 80% of the rated sessions fulfilled the benchmark for good MI on the relational summary score, 67% for the technical summary score, 76% of the rated sessions fulfilled benchmarks for the summary score of percent complex reflections, and 47% of rated session the reflection to question ratio. All in all, these indicate high levels of fidelity and are comparable to other studies with high levels of fidelity to MI (Boman et al, 2018;Freira et al, 2018;Magill, Graves, et al, 2018;Owens et al, 2017;Serrano et al, 2017) and substantially higher than studies with expected lower fidelity to MI (Copeland et al, 2018;Simper, Breckon, and Kilner, 2017). The ratings indicated use of MIA's, but the general low ratings of emphasize autonomy questions the use of this important MI-technique in this study.…”
Section: Fidelity To MIsupporting
confidence: 86%
“…45 A brief review of recent studies on the effectiveness of MI in pediatric obesity are presented in Table 4. 5,[52][53][54][55] Two trials each on adolescents and children were identified. Three of the four studies were relatively brief, ranging from 3-10 sessions, [52][53][54] while the Fit Families trial was a more intensive…”
Section: Recent MI Interventionsmentioning
confidence: 99%
“…5 The results imply that brief forms of MI counseling may be useful in treating pediatric obesity. [52][53][54] Brief interventions were effective, and more intensive intervention was not more beneficial.…”
Section: Recent MI Interventionsmentioning
confidence: 99%
“…On the other hand, it is reported that inactivity-related conditions, such as obesity, may cause health problems and contribute to energy imbalance (Hormazábal-Peralta et al, 2018). Over the last decade, it has been observed that it has a more pronounced effect on metabolic complications because of the increasing tendency in obesity (Freira et al, 2018). These explanations may lead to be in favor of AG, depending on increased energy usage for daily physical activity (NG≤PG<AG; p<0.05; Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and its metabolic results represent one of the five global risks that lead to hyperglycemia, high blood pressure, cardiovascular morbidity, and mortality, as well as tobacco use and physical inactivity (Hofsø et al, 2010). In the last decade, it is estimated that this generation will be the first generation to live shorter than their parents in human history because of the upward trend in obesity is more than expected (Freira et al, 2018). In addition, obesity is considered a public health problem that can cause many emotional and social effects, such as difficulties in relationship, depression and low self-esteem, as well as difficulties in health problems (Barbosa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%